Asymptomatic Tremendous Lung Shadow in a Young Man: A Case Report - Li Min Wang (Journal of Global Pharma Technology, 2020)
The study is devoted to a unique asymptomatic case of pulmonary sequestration with no infection detected and offers an appropriate treatment solution.The study was carried out in the Surgery Department of the polyclinic No.47011661433010211A1001, Hangzhou, China, in 2019. The patient diagnosed with pulmonary sequestration was 26 years old. No associated symptoms were detected. CT Angiography (CTA) was applied to diagnose pulmonary sequestration, whereas Digital Subtraction Angiography (DSA) was conducted before operation in order to localize abnormal vessels. CT Angiography (CTA) suggested thickening and tortuous regional arteries in the right lower lung, with obvious increasing in branches. The 12th thoracic level aorta branched out into the right lower lobe of the lung, the vein drained back into the pulmonary vein. The surgical treatment of pulmonary sequestration was performed with the embolic thread and involved embolization with an embosphere of 0.5 mm diameter and a spring coil. The post-surgical angiography revealed the disappearance of distal blood flow, indicating success of the therapy. After the intervention, the patient developed a recurrent fever. After the oral administration of low-dose glucocorticoids, the patient’s body temperature dropped to the normal level. The final CT scan of the chest conducted a year after treatment showed shadow absorption.The embolization therapy turned out to be effective and hence is suitable for the treatment of pulmonary sequestration. It was established that lung malformations may manifest as an asymptomatic condition. This finding expands what we know about the pulmonary sequestration. Keywords: Pulmonary sequestration; Interventional embolization, Angiography, Clinical case.